Impact of HVOF sprayed Vanadium Carbide (VC) based novel coatings on slurry erosion behaviour of hydro-machinery SS316 steel. (December 2022) - Singh, Vikrant; Singla, Anil Kumar; Bansal, Anuj
Abstract: In this research work, different compositions of VC (Vanadium Carbide) +CuNi-Cr (Cupronickel-Chromium) ranging from 0% to 100% were deposited over hydro-machinery steel (SS316) with the help of HVOF spraying system. The slurry erosion for different composition of coatings and bare SS316 steel have been evaluated with the help of slurry erosion testing machine. From the experiments, it was concluded that amongst all the developed coatings, 100% VC based coating has shown exceptionally good resistance to slurry erosion as compared to other composition of coatings owing to extra microhardness attained by VC granules. Brittle mode of erosion mode was observed for coating with VC as major constituent, which was reported to be converted to ductile mode with the increase in CuNi-Cr addition percentage.